An empirical study of liquidity and information effects of order flow on exchange rates - Francis Breedon; Paolo Vitale (European Central Bank (ECB), 2004)
We propose a simple structural model of exchange rate determination which draws from the analytical framework recently proposed by Bacchetta and van Wincoop (2003) and allows us to disentangle the liquidity and information effects of order flow on exchange rates. We estimate this model employing an innovative transaction data-set that covers all direct foreign exchange transactions completed in the USD/EUR market via EBS and Reuters between August 2000 and January 2001. Our results indicate that the strong contemporaneous correlation between order flow and exchange rates is mostly due to liquidity effects. This result also appears to carry through to the four FX intervention events that appear in our sample.
Keywords: D82; G14; G15; 330; Exchange Rate Dynamics; Foreign Exchange Micro Structure; order flow